High-strain zone deformation in the southern Capricorn Orogen, Western Australia: kinematics and age constraints - Reddy, Steven; Occhipinti, Sandra (Elsevier, 2004)
Detailed structural mapping of a the Kerba Fault, a high-strain zone along the contact between the Archaean to Palaeoproterozoic Yarlarweelor Gneiss Complex (partly derived from the Yilgarn Craton) and the Palaeoproterozoic volcano-sedimentary rocks of the Bryah Group, indicate a temporal progression from foliation development to folding and finally brittle deformation. Structural data from the penetrative S1 foliation indicate a superficially simple geometry and kinematic history with a single, pervasive, greenschist facies foliation forming during dextral strike slip shearing. However, systematic spatial variations in the magnitude and orientations of mineral elongation lineations indicate a more complex deformation history involving a combination of general transpressive dextral shear and subsequent reactivation. This deformation has previously been considered to develop between 1830 and 1780 Ma ago during the Capricorn Orogeny. Relative age relationships around the Kerba Fault indicate that the high-strain deformation postdates the intrusion of the Kerba Granite at 18086 Ma. Analysis of available age data indicates that the minimum age of deformation is poorly constrained. However, evidence from regionally similar structures and geochronological data indicate that deformation associated with high-strain zones in the southern Capricorn Orogen may be Mesoproterozoic in age--significantly younger than the Capricorn Orogeny.